The manhattan projects (2012), volume 2 ebook - Hickman, Jonathan (The Manhattan Projects (2012), 2015)
140-Pages! Collects The Manhattan Projects 6-10! The second amazing volume of the SCIENCE, BAD book of the new millennium. The battle for global supremacy is underway and the bad men of the Manhattan Projects will only accept one outcome: World domination Collecting the coolest new series of the year into one super science package.. Author: Jonathan Hickman. Illustrator: Nick Pitarra . 2013 Jonathan Hickman & Nick Pitarra.